2012
DOI: 10.4309/jgi.2012.27.7
|View full text |Cite
|
Sign up to set email alerts
|

Shame-prone gamblers and their coping with gambling loss

Abstract: Applying recent research on self-conscious emotions (e.g., Tangney & Dearing, 2002) to the literature of gambling, the proposal that painful self-conscious emotions brought about by chronic awareness of personal inferiority and inadequacy, deemed as a major predisposing factor for problem gambling (Jacobs, 1986), appears to be compatible with the chronic affective trait of shameproneness but incompatible with guilt-proneness. This premise led to the hypothesis that shame-proneness is strongly associated with p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 35 publications
2
7
0
Order By: Relevance
“…First, description of vulnerable narcissistic individuals encompasses specific characteristics which seem to be shared by addicted gamblers. For instance, shame is often a self-reported emotion in this clinical population and proneness to experience feelings of shame in interpersonal situations has been related to chasing behavior (Yi 2012). Shame experienced by individuals with high vulnerable narcissistic traits is related to their own ambitions or needs.…”
Section: Constantmentioning
confidence: 99%
“…First, description of vulnerable narcissistic individuals encompasses specific characteristics which seem to be shared by addicted gamblers. For instance, shame is often a self-reported emotion in this clinical population and proneness to experience feelings of shame in interpersonal situations has been related to chasing behavior (Yi 2012). Shame experienced by individuals with high vulnerable narcissistic traits is related to their own ambitions or needs.…”
Section: Constantmentioning
confidence: 99%
“…high alcohol consumption, smoking) have been linked to gambling generally and at harmful levels (Mcgrath and Barrett, 2009). Consumption of substances such as alcohol and tobacco may reinforce cravings and reward of other addictive behaviours (Mcgrath and Barrett, 2009), as well as a way of coping with gambling losses (Yi, 2012). Smoking has also been associated with habitual forms of gambling (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted by Gupta and Derevensky (1998) showed that adolescent and high school gamblers who were classified as problem or pathological gamblers reported more emotion focused coping strategies, such as dissociation and gambling to escape compared to non-problem gamblers. Other studies have focused on the development of depressive symptoms as a consequence of gambling behavior, which in turn can also lead to higher motivation to gamble to relieve negative mood (Yi 2012;Yi and Kanetkar 2011). For instance, Yi and Kanetkar (2011) asked participants to recall past gambling loss and the feelings associated with those experiences.…”
Section: Motivation Self-efficacy and Gambling Behaviormentioning
confidence: 99%